2019
DOI: 10.1186/s13046-019-1401-y
|View full text |Cite|
|
Sign up to set email alerts
|

Elevated TRIP13 drives the AKT/mTOR pathway to induce the progression of hepatocellular carcinoma via interacting with ACTN4

Abstract: Background: ATPase associated with a variety of cellular activities (AAA ATPase) family members are closely linked to tumor formation and progression. However, their roles in hepatocellular carcinoma (HCC) largely remain unclear. Methods: Bioinformatic analyses of public databases were used to excavate the potential AAA ATPases that may contribute to HCC, and thyroid hormone receptor interactor 13 (TRIP13) was selected to following researches because of its most prominently differential expression. Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 34 publications
(39 reference statements)
2
40
0
Order By: Relevance
“…In hepatocellular carcinoma (HCC) cells, TRIP13 knockdown increases levels of the epithelial marker, E‐cadherin, and decreases the mesenchymal markers, vimentin, and snail. Thus, in HCC cells, TRIP13 promotes metastasis via inducing the EMT [53]. Further, in bladder cancer cells, TRIP13 knockdown increases E‐cadherin and decreases N‐cadherin and Snail [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hepatocellular carcinoma (HCC) cells, TRIP13 knockdown increases levels of the epithelial marker, E‐cadherin, and decreases the mesenchymal markers, vimentin, and snail. Thus, in HCC cells, TRIP13 promotes metastasis via inducing the EMT [53]. Further, in bladder cancer cells, TRIP13 knockdown increases E‐cadherin and decreases N‐cadherin and Snail [54].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that TRIP13‐depleted CRC cells had less activity for β‐catenin as well as lower levels of LEF1 and TCF1. In HCCs, it was shown that TRIP13 regulates the WNT/β‐catenin pathway [53]. For CRCs, cyclin D1, a Wnt target gene, is transcriptionally activated by β‐catenin [68].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the miR-192 promoter is hyper-methylated, which leads to the transcriptional repression of miR-192-5p in HCC cell lines and primary CSC + HCC ( Gu et al, 2019 ). Besides, Zhu and coworkers reported that miR-192-5p is an upstream regulator of thyroid hormone receptor interactor 13 (TRIP13), a promising oncogene in HCC, by directly targeting the 3′-UTR of TRIP13 mRNA, thereby inhibiting the progression of HCC ( Zhu et al, 2019 ). Interestingly, the expression of miR-192-5p is also regulated by other molecules in HCC, including circRNA, although increasing evidence has demonstrated that numerous molecules are influenced by miR-192-5p ( Qiu et al, 2019 ).…”
Section: Mir-192-5p In Human Diseasesmentioning
confidence: 99%
“…shACTN4 suppresses the Akt/GSK-3β/β-catenin signaling, and ACTN4 interacts with β-catenin in breast cancer stem cells ( Wang et al, 2017 ). In addition, the ACTN4 and TRIP13 complex promotes EMT and tumor metastasis through the Akt signaling in hepatocellular carcinoma cells ( Zhu et al, 2019 ). We have previously reported that ACTN4 induces the phosphorylation of Akt and GSK-3β in cervical cancer ( An et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%